Med konstruktivističnim in pluralističnim modernizmom - prispevek k umevanju Osterčevega kroga - Salmič Kovačič, Karmen (Muzikološki zbornik, 2019)
The theme of this article was inspired by a series of questions that arise to researchers when discussing compositions by musical modernist Slavko Osterc and his pupils from the first half of the 20th century, whose music was neither "tonal" nor extreme "atonal". On the one hand, there is a strong doubt of the Slovenian analysts in the progress (modernity) of the compositional means of the mentioned music, since the works are usually compared with the most extreme solutions of the Second Vienesse School - with atonality, athematicism or twelve-tone technique, and on the other hand the rejection of this music from the Slovenian cultural management in concert performing. The central question that arises is the question of the meaningfulness of such comparison, given that these composers were educated also in Prague and did not want to follow the Schönberg's twelve-tone method.
Keywords: 20th century; Alois Haba; Arnold Schonberg; Arnold Schönberg; glasba 20. stoletja; glasbeni modernizem; musical modernism; Osterčev krog; Slavko Osterc's circle; Slovene music; slovenska glasba